2013
DOI: 10.4039/tce.2013.46
|View full text |Cite
|
Sign up to set email alerts
|

Modelling factors that affect the presence of larval mosquitoes (Diptera: Culicidae) in stormwater drainage systems to improve the efficacy of control programmes

Abstract: Stormwater catch basins form part of artificial drainage systems in urban areas and can provide larval habitat for mosquito vector species of West Nile virus (WNv), such as Culex pipiens Linnaeus (Diptera: Culicidae). We evaluated the impact of management techniques and targeted applications of larvicide on larval populations of this potential WNv mosquito vector species in catch basins from the Lower Mainland of Vancouver and on Vancouver Island of British Columbia, Canada. A mixed effects logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Stormwater catch basins are common sources of permanent or semipermanent standing water that are routinely targeted for mosquito larvicide applications by local mosquito control programs to reduce local mosquito populations and incidence of mosquito-borne diseases. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] A common practice is to treat the stagnant water in all or most of the tens of thousands or sometimes hundreds of thousands of basins that can exist in an agency's operational area with at least one application of an extended-release larvicide formulated to last up to 150-180 days. Since the mid-1990s, extended-release larvicides (eg, Altosid® XR, FourStar®, and Natular™ XRT) have been used by the North Shore Mosquito Abatement District (NSMAD), a publicly funded mosquito control agency serving the northeast Chicago metropolitan area, to reduce mosquitoes in ∼50,000 catch basins each season.…”
Section: Introductionmentioning
confidence: 99%
“…Stormwater catch basins are common sources of permanent or semipermanent standing water that are routinely targeted for mosquito larvicide applications by local mosquito control programs to reduce local mosquito populations and incidence of mosquito-borne diseases. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] A common practice is to treat the stagnant water in all or most of the tens of thousands or sometimes hundreds of thousands of basins that can exist in an agency's operational area with at least one application of an extended-release larvicide formulated to last up to 150-180 days. Since the mid-1990s, extended-release larvicides (eg, Altosid® XR, FourStar®, and Natular™ XRT) have been used by the North Shore Mosquito Abatement District (NSMAD), a publicly funded mosquito control agency serving the northeast Chicago metropolitan area, to reduce mosquitoes in ∼50,000 catch basins each season.…”
Section: Introductionmentioning
confidence: 99%
“…As part of efforts to decrease local vector populations of West Nile virus (WNV) and other mosquito-borne diseases, stormwater catch basins are often targeted for routine larvicide applications in urban areas around the world. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The North Shore Mosquito Abatement District (NSMAD) treats approximately 50,000 catch basins each season in the District's 207 sq km (80 sq mi) located in the northeastern greater Chicago IL metropolitan area. Treatment is with extended-release, 180-day larvicides, and the specific objective is to reduce local populations of the local WNV vectors Culex pipiens and Cx.…”
Section: Introductionmentioning
confidence: 99%
“…In urbanized areas throughout the world, catch basins (subsurface vaults designed to capture urban storm water runoff) are common habitats for the aquatically confined immature stages of vector mosquito species. [1][2][3][4][5][6][7] In the United States, West Nile virus (WNV) vector species in the Culex pipiens complex are found consistently within these structures, making catch basins an important focus of local vector control programs. [8][9][10][11] In some urbanized regions, including the Chicago metropolitan area, these structures may even be the most prevalent source of these species.…”
Section: Introductionmentioning
confidence: 99%
“…For example, larger rainfall events or catch basins prone to higher volumes and/or intensity of runoff may "flush" mosquitoes out of basins resulting in decreased larval abundance in the following days. [17][18][19] Jackson et al 4 found catch basins surrounded predominately by pavement were less likely to hold larvae than those with nearby trees or grassy areas. Indeed, Gardner et al 20 observed certain environmental features, including ammonia and nitrates in basin water, and the area of all shrubs of height ,1 m surrounding the catch basins were positively associated of high larval abundance, whereas pH and area of flowering shrub were negatively associated with larvae.…”
Section: Introductionmentioning
confidence: 99%